2017
DOI: 10.1371/journal.pone.0187882
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary immune responses to Mycobacterium tuberculosis in exposed individuals

Abstract: BackgroundBlood based Interferon-(IFN)-γ release assays (IGRAs) have a poor predictive value for the development of tuberculosis. This study aimed to investigate the correlation between IGRAs and pulmonary immune responses in tuberculosis contacts in Germany.MethodsIGRAs were performed on bronchoalveolar lavage (BAL) cells and peripheral blood from close healthy contacts of patients with culturally confirmed tuberculosis. Cellular BAL composition was determined by flow cytometry. BAL cells were co-cultured wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Although few if any studies have measured the BAL cell response to bacterial pathogens in CF, some have been performed for other disease states. In those cases, many have involved stimulating BAL cells with proteins, heat‐treated bacteria or bacterial lysate, 20‐22 with exceptions often being those involving slow‐growing bacteria such as mycobacteria 23 . While informative, lysing, or heat‐treating bacteria could release PAMPs, normally contained within the structure of the cell (ie LPS, peptidoglycan, lipopeptides, DNA and RNA) 24 possibly facilitating increased TLR ligand activation as compared to live bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although few if any studies have measured the BAL cell response to bacterial pathogens in CF, some have been performed for other disease states. In those cases, many have involved stimulating BAL cells with proteins, heat‐treated bacteria or bacterial lysate, 20‐22 with exceptions often being those involving slow‐growing bacteria such as mycobacteria 23 . While informative, lysing, or heat‐treating bacteria could release PAMPs, normally contained within the structure of the cell (ie LPS, peptidoglycan, lipopeptides, DNA and RNA) 24 possibly facilitating increased TLR ligand activation as compared to live bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…In those cases, many have involved stimulating BAL cells with proteins, heat-treated bacteria or bacterial lysate, [20][21][22] with exceptions often being those involving slow-growing bacteria such as mycobacteria. 23 While informative, lysing, or heat-treating bacteria could release PAMPs, normally contained within the structure of the cell (ie LPS, peptidoglycan, lipopeptides, DNA and RNA) 24 possibly facilitating increased TLR ligand activation as compared to live bacteria. Hence, such stimulations might not necessarily trigger the same activation pathways in vitro, as occur with live pathogenic bacteria, as in the lung.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have confirmed an overactive immune system in severe COVID-19 patients that correlates with patient mortality. Infections with TB reprogram the macrophages to secrete a distinct set of cytokines (Herzmann et al, 2017). Moreover, macrophages subpopulations have been identified to exert a possible anti-inflammatory or pro-inflammatory response that is identifiable by their distinct metabolomics signature.…”
Section: Comparison With Published Metabolomics Dataset Featuring Pro...mentioning
confidence: 99%
“…In contrast, the risk to develop TB disease in these young infants was associated with an increased circulation of activated CD4 + T cells, suggesting a possible contribution of early immune activation to disease susceptibility . Intriguingly, stronger cellular responses were detected as preactivated lymphocytes and increased Th1 cytokine production but impaired macrophage activation in bronchoalveolar lavage (BAL) from individuals with latent TB compared healthy exposed individuals . The balance in protective versus pathogenic CD4 + T‐cells responses in different phases of TB infection and disease will certainly be an interesting subject for further exploration.…”
Section: Effector Cells Subsets Involved In Protective Tb Immunitymentioning
confidence: 99%